2017
DOI: 10.1186/s12913-017-2056-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of work pressure and associated factors influencing hospital nurse turnover: a cross-sectional investigation in Shaanxi Province, China

Abstract: BackgroundNurses' turnover is a major contributor to nursing shortages, strongly influenced by nurses’ intentions to leave. Several factors influencing the turnover intention have been well identified in Western countries and large cities in China. However, whether these factors also contribute to nurses' work stress in Midwest China are still unclear. The main purpose of this study was to examine the work pressure and associated factors influencing the nurses’ intent to leave.MethodsA cross-sectional question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 39 publications
4
74
3
Order By: Relevance
“…Organisations provide various forms of rewards to employees in exchange for their contributions. It is reported that nurses perceived whether their organisations were rewarding their efforts monetarily or nonmonetarily, which influenced their decisions to leave or remain (Li, Galatsch, Siegrist, Müller, & Hasselhorn, 2011;Yang et al, 2017). At first, basic monetary rewards, such as salaries, bonuses and incentives through a contract between the organisation and the employee (Williams, Brower, Ford, Williams, & Carraher, 2008), are critically important factors for encouraging employees' retention and motivation (El-Jardali et al, 2009;Tekleab, Bartol, & Liu, 2005).…”
Section: What Does This Paper Contribute To the Wider Global Clinicalmentioning
confidence: 99%
See 2 more Smart Citations
“…Organisations provide various forms of rewards to employees in exchange for their contributions. It is reported that nurses perceived whether their organisations were rewarding their efforts monetarily or nonmonetarily, which influenced their decisions to leave or remain (Li, Galatsch, Siegrist, Müller, & Hasselhorn, 2011;Yang et al, 2017). At first, basic monetary rewards, such as salaries, bonuses and incentives through a contract between the organisation and the employee (Williams, Brower, Ford, Williams, & Carraher, 2008), are critically important factors for encouraging employees' retention and motivation (El-Jardali et al, 2009;Tekleab, Bartol, & Liu, 2005).…”
Section: What Does This Paper Contribute To the Wider Global Clinicalmentioning
confidence: 99%
“…There is much interest in the reasons nurses leave their current job and the effective strategies for retaining the nursing workforce internationally (Han, Trinkoff, & Gurses, 2015;Takase, Teraoka, & Yabase, 2016;Yang, Lv, Zhou, Liu, & Mi, 2017). Any turnover rate below 15% annually is considered healthy and not a cause for concern (Kenny, 2007); meanwhile, high turnover rates make major problems in the healthcare system and quality of care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retention of hospital staff nurses has been identified as a key factor to counteract the shortage (Baumann, 2010;International Council of Nurses 2014;Shacklock & Brunetto, 2012). Empirical studies have highlighted the significant effect of job stress on retention and turnover intention among nurses (Wu, Fox, Stokes, & Adam, 2012;Yang, Lv, Zhou, Liu, & Mi, 2017;Zhang, Wu, Fang, Zhang, & Wong, 2017). As the pressure on the healthcare system is rapidly increasing with population ageing, evidence concerning the job stress to turnover pathway is urgently needed to develop effective interventions.…”
Section: )mentioning
confidence: 99%
“…Long working hours, high workload, lack of job security, high workplace noise, too much heat or cold at workplace, job hazards and possibility of injury, working methods, inadequate facilities for work, low light and the existence of toxic gases in the workplace, the relationship with superior colleagues and subordinates at work, and work conflicts are of the main factors in stress creation in the hospital spaces (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%